Performance of InGaN-Based Thin-Film LEDs With Flip-Chip Configuration and Concavely Patterned Surface Fabricated on Electroplating Metallic Substrate - Xiao-Long Hu; Zhao-Yi Qi; Hong Wang; Xi-Chun Zhang (IEEE Photonics Journal, 2016)
In this paper, a p-pad-up InGaN-based flip-chip (FC) thin-film light-emitting diode (TFLED) on electroplating metallic substrate was fabricated by a combination of electrodes isolation, FC configuration, copper electroplating, and laser lift-off techniques. This allowed formation of n-contacts on Ga-polar n-GaN and superior design of n-electrode pattern, resulting in an improved electrical performance when compared with the vertical-structure (VS) TFLED, in which the n-contacts need to be formed on N-polar n-GaN. In addition, the light output power was enhanced through this architecture due to the uniform current distribution and the absence of pads and wires on top of the FC-TFLEDs. It is found that the wall-plug efficiency of the FC-TFLEDs is 23.6% higher than that of the VS-TFLEDs. Moreover, the FC-TFLEDs with a concavely patterned surface were fabricated from the LED wafer with patterned sapphire substrate. Further improvement in output power was achieved when compared with that of the FC-TFLED fabricated from the LED wafer with flat sapphire substrate.